Hydrolysis of L-Histidine Methyl Ester - Cole, E. R (Thrombosis and Haemostasis, 1968)
The ratio of TAME esterase activity (or PME esterase activity for α-chymotrypsin) to HME esterase activity has been determined for a number of proteolytic enzymes under identical conditions. Papain showed no attack on HME, but ficin, bromelin, human plasmin, trypsin, thrombin, autoprothrombin C, urokinase and α-chymotrypsin hydrolyze this substrate to varying degrees. Ficin showed a TAME/HME activity ratio of 304 while the lowest ratio (approximately 1) was found for urokinase, an activator of plasminogen. This high relative affinity of urokinase for HME prompted an investigation to determine if this property was also a function of streptokinase-activator complex. Glycerol-activated plasmin had a low relative affinity for HME as a substrate (TAME/HME = 157), but addition of high concentrations of streptokinase increased the relative affinity of the preparation for HME catalysis by 500 to 600% (TAME/HME = 26.4). Human plasminogen activated by high concentrations of streptokinase also demonstrate high relative affinity for HME (TAME/ HME = 20-25). HME esterase activity is largely lost when streptokinase is destroyed by pH 2.0 treatment, but can be regained by readdition of streptokinase to the plasmin preparation. Hydrolysis of HME by plasmin preparations in the presence of streptokinase is believed to be primarily a property of streptokinase-plasmin complex.